2003
DOI: 10.1021/jp030178i
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra and Quantum-Chemical Studies of Disilylmethanes

Abstract: New infrared data are reported for disilylmethane-d 0 and -d 6 in the gas phase. Quantum-chemical (QC) calculations have been carried out at HF, MP2, and B3LYP levels with a variety of basis sets. These verify the previously obtained experimental C 2 v structure. The two possible kinds of SiH bonds are identical in strength but not in electrical properties. Reassignments are made of several vibration frequencies. The A2 and B2 torsional frequencies are estimated to be 78.5 and 133 cm-1, respectively, from co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
0
21
1
Order By: Relevance
“…These two A 2 vibrations are calculated to have the weakest infrared intensities among the fundamentals for the four molecules and thus were difficult to assign without the DFT calculations. Several other studies have employed DFT calculations to predict vibrational frequencies and to compare them with previous experimental results for some noncyclic silicon-containing molecules including dimethylsilane, , trimethylsilane, , disilylmethane, , and ethylsilane . These studies utilized the calculated frequencies to reinvestigate some of the uncertain aspects of the vibrational spectra recorded many years earlier, but none of these studies noted why such a discrepancy between the experimental and calculated frequencies for these CH 2 out-of-phase modes should occur. Nevertheless, one conclusion drawn from all these studies as well as our own is that the presence of a silicon atom in the structure of a molecule does not adversely affect the accuracy of the vibrational frequencies calculated by the DFT method.…”
Section: Vibrational Assignmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These two A 2 vibrations are calculated to have the weakest infrared intensities among the fundamentals for the four molecules and thus were difficult to assign without the DFT calculations. Several other studies have employed DFT calculations to predict vibrational frequencies and to compare them with previous experimental results for some noncyclic silicon-containing molecules including dimethylsilane, , trimethylsilane, , disilylmethane, , and ethylsilane . These studies utilized the calculated frequencies to reinvestigate some of the uncertain aspects of the vibrational spectra recorded many years earlier, but none of these studies noted why such a discrepancy between the experimental and calculated frequencies for these CH 2 out-of-phase modes should occur. Nevertheless, one conclusion drawn from all these studies as well as our own is that the presence of a silicon atom in the structure of a molecule does not adversely affect the accuracy of the vibrational frequencies calculated by the DFT method.…”
Section: Vibrational Assignmentsmentioning
confidence: 99%
“…Several other studies have employed DFT calculations to predict vibrational frequencies and to compare them with previous experimental results for some noncyclic silicon-containing molecules including dimethylsilane, , trimethylsilane, , disilylmethane, , and ethylsilane . These studies utilized the calculated frequencies to reinvestigate some of the uncertain aspects of the vibrational spectra recorded many years earlier, but none of these studies noted why such a discrepancy between the experimental and calculated frequencies for these CH 2 out-of-phase modes should occur. Nevertheless, one conclusion drawn from all these studies as well as our own is that the presence of a silicon atom in the structure of a molecule does not adversely affect the accuracy of the vibrational frequencies calculated by the DFT method. Moreover, for disilylmethane (CH 3 SiH 2 CH 3 ), the CH 2 twisting vibration was previously predicted with the B3LYP/6-311G(d,p) level of theory to be at 1043 cm −1 , which is at a somewhat lower value than had been assigned before (1101 cm −1 ).…”
Section: Vibrational Assignmentsmentioning
confidence: 99%
“…14 The sample was purified several times and the identity and the purity of the compound were confirmed by 1 H, 13 C and 19 F NMR and by infrared spectroscopy. The chloro derivative was prepared by the reaction of trichlorosilane with trichlorovinylsilane.…”
Section: Sample Preparationmentioning
confidence: 99%
“…However, for DSB the discrepancies from the observed values were considerable. 19 A normal coordinate analysis based on harmonic force constants derived from the DFT calculations was carried out as described below. Applying the much larger cc-pVQZ basis sets, however, the wavenumbers 1295 and 1298 cm 1 were obtained for 14 .…”
Section: Normal Coordinate Calculationsmentioning
confidence: 99%
“…Several such studies have been reported for silyl compounds using density functional theory in the B3LYP approach with the basis set 6-311G**. 4,5…”
Section: Introductionmentioning
confidence: 99%